Co-infection with Anaplasma platys, Bartonella henselae, Bartonella koehlerae and 'Candidatus Mycoplasma haemominutum' in a cat diagnosed with splenic plasmacytosis and multiple myeloma. Issue 8 (August 2014) - Qurollo, Barbara A; Balakrishnan, Nandhakumar; Cannon, Coralie Zegre; Maggi, Ricardo G; Breitschwerdt, Edward B
Anaplasma platys ( Apl ), ' Candidatus Mycoplasma haemominutum' ( C Mh), Bartonella henselae ( Bh ) and Bartonella koehlerae ( Bk ) were confirmed by polymerase chain reaction (PCR) amplification and DNA sequencing in a cat diagnosed with multiple myeloma. Other inconsistently documented hematologic abnormalities included anemia, thrombocytopenia, eosinophilia and hypoglycemia. Persistent Apl infection was confirmed for the first time in a North American cat by sequencing three bacterial genes ( 16S rRNA, p44 and GroEL ) in peripheral blood samples collected 100 days apart. Following doxycycline treatment for Apl, multiple myeloma was diagnosed based upon a monoclonal gammopathy and splenic plasmacytosis, and the cat was treated with melphalan, chlorambucil and prednisolone. Apl DNA was not amplified from post-treatment blood samples and the hyperglobulinemia resolved temporarily following chemotherapy. Retrospective PCR analysis of stored DNA extracts identified C Mh, Bk and Bh infections. Retrospective PCR for antigen receptor rearrangements (PARR) of splenic aspirates did not confirm B- or T-cell clonality. Co-infection with multiple vector-borne pathogens should be a diagnostic consideration in cats with chronic hypergammaglobulinemia, monoclonal gammopathy and splenic plasmacytosis.